1977
DOI: 10.1016/s0006-3495(77)85598-7
|View full text |Cite
|
Sign up to set email alerts
|

Neural repetitive firing: modifications of the Hodgkin-Huxley axon suggested by experimental results from crustacean axons

Abstract: The Hodgkin-Huxley equations for space-clamped squid axon (18 degrees C) have been modified to approximate voltage clamp data from repetitive-firing crustacean walking leg axons and activity in response to constant current stimulation has been computed. The m infinity and h infinity parameters of the sodium conductance system were shifted along the voltage axis in opposite directions so that their relative overlap was increased approximately 7 mV. Time constants tau m and tau h, were moved in a similar manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
163
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(167 citation statements)
references
References 29 publications
3
163
0
1
Order By: Relevance
“…Model equations are described in ref. 3. Briefly, the model is composed of a leak current I leak , a transient sodium current I Na , a delayed-rectifier potassium current I Kd , and a transient A-type potassium current I A .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model equations are described in ref. 3. Briefly, the model is composed of a leak current I leak , a transient sodium current I Na , a delayed-rectifier potassium current I Kd , and a transient A-type potassium current I A .…”
Section: Methodsmentioning
confidence: 99%
“…Experimentally, this means the frequency-input current (or FI) curve has a specific shape, called Type I, such that firing frequency smoothly approaches zero at current threshold (1-6). By contrast, so-called Type II neurons have a lower bound in their firing frequency and move abruptly from quiescence to fast spiking, with this transition visible as a sharp jump in the FI curve at threshold (1,3,5).Type I behavior is physiologically unlikely with a minimal set of membrane currents such as the voltage-gated sodium and delayed-rectifier potassium currents in the standard squid giant axon Hodgkin-Huxley model, which is Type II. Classic experimental (1, 7) and theoretical studies (3-5, 8, 9) revealed that a Type II membrane (such as a squid giant axon) can be turned into a Type I membrane by adding an inactivating (A-type) potassium conductance, I A .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…channels in higher organisms have been shown to regulate the discharge patterns of neurons, and the transient K? channels (Connor and Stevens 1971;Connor et al 1977;Wellnitz 2010) were then added to the original HH model. Thus, the modulation model from the HH equation systems (Hodgkin and Huxley 1952) GðV; m; n; hÞ ¼ G Na m…”
Section: Transduction and Modulationmentioning
confidence: 99%
“…channels were referred to Hodgkin and Huxley (1952) and Connor et al (1977), and e(t) the normal Gaussian noises. The drive current I c was the sensing current by external stimulus (lA/cm 2 ), which was calculated by Eq.…”
Section: Transduction and Modulationmentioning
confidence: 99%